Effect of printing process parameters on tensile strength and wear rate of 17-4PH stainless steel deposited using SLM process (Fracture and Structural Integrity, 2024)
In the current work 17-4PH Stainless Steel is deposited using SLM process. It is widely used to build structural parts appropriate for automotive, medical, and aerospace applications. The 17-4 PH SS samples were deposited using technical parameters such as laser power: LP, Scan speed: SS, and hatch distance: HD) were studied to analyze the wear rate and ultimate tensile strength. Fracture and wear track analysis was performed using SEM analysis. The DOE-Taguchi method is applied for the experimental plan and analysis of the parametric contribution with a statistical evaluation technique: Pareto Analysis of variance. The fracture surface morphology of 17-4 PHSS samples at different conditions indicated different failure. 17-4 PHSS samples LP1SS1HD1 condition displayed ductile-brittle fracture followed by LP3SS3HD2 and LP3SS3HD3 conditions displaying ductile failure. The wear features indicate abrasive pits and thin grooves across few areas reduced intensity of wear compared to the extensive wear-out surface observed at conditions. The optimized conditions are validated and recommended to industry personnel for reference.
Keywords: 17-4PH stainless steel; Tensile strength; Fracture studies; SLM process; Super Ranking Concept.